ANALISIS KUALITAS KOMBINASI VACUUM RESIDUE DAN HOT ROLLED SHEET PADA INFRASTRUKTUR JALAN - Ansyory, Deby; Jimmyanto, Hendrik; Misdalena, Felly; Ramadhani (LATERAL: Jurnal Teknik Sipil, 2024)
Roads are infrastructure that function as a link between one region and another that is used by the general public, and is passed by various types of motorized vehicles. Road pavement damage often occurs before reaching the design age due to peeling due to excessive moisture. The use of vacuum residue (VR) in hot rolled sheet (HRS) mixtures for road construction involves several important technical and economic considerations. This study analyzed the Marshall characteristics of HRS mixture properties using VR. The VR used came from AMP PT. Pertamina Persero with an average asphalt content of 5.88%. The results showed that the Marshall parameters that did not meet were voids in the mixture (VIM) and voids filled with asphalt (VFA), for other parameters had met the 2018 Bina Marga specifications. The Marshall stability value obtained was 1979.55 kg with a Marshall Quotient of 395.91 kg / mm. Based on the results obtained, it shows that the use of VR in the HRS mixture can increase the Marshall stability value.